Analysis and Exploration of Hypermedia-Based Learning Materials Proyek IPAS in Grade 10 Vocational High School - Auliya Naimah; Robinson Situmorang; Dwi Kusumawardani (CV. Media Digital Publikasi Indonesia, 2025)
One of the innovations arising from technological developments is using hypermedia in learning. Therefore, this study aims to identify learning needs in the development of hypermedia-based Proyek IPAS learning materials in Class X vocational schools. The research method used is Research and Development (R&D), the development model used in this study combines the Dick and Carey and Lee & Owens models, which focus on the development of hypermedia-based Proyek IPAS learning materials, both of which were chosen because they complement each other in the development of technology-based learning materials, especially in multimedia learning such as hypermedia. Data collection techniques used observation, questionnaire interviews, and learning outcomes tests. The results showed that students aged 15-16 can use technological devices such as laptops, tablets, and smartphones, but are more often used for entertainment than learning. Observations revealed the limitations of available learning materials, so interactive and appropriate hypermedia-based Proyek IPAS learning materials are needed. This research provides a basis for developing innovative and relevant hypermedia-based Proyek IPAS learning materials to support project-based learning in vocational high schools.